Management of the Tahfidz Excellence Class Program - Aji, Wibakti Restu; Masrifatin, Yuni (STAI Miftahul Ula Nganjuk, 2023)
The study by Az Zahrah, 'Ainun Shofiyatu (2023) investigates the implementation of flashcards in Arabic language learning to enhance interest in vocabulary acquisition among eighth-grade students at MTs Darul Muta'allimin Patianrowo. The study aims to describe the implementation of flashcards in Arabic language teaching, assess students' interest in vocabulary learning, and evaluate the effectiveness of flashcards in improving learning outcomes. This qualitative research employs interviews, observations, and documentation for data collection. The findings indicate that flashcards were effectively implemented, leading to easier comprehension of the material. Supporting factors include competent teachers, appropriate teaching media, adequate facilities, motivated students, and a conducive learning environment. Challenges include diverse educational backgrounds, varying student characteristics, different abilities, and fluctuating levels of motivation. Overall, the use of flashcards significantly increased students' interest and engagement in vocabulary learning